Pengaruh pengendalian risiko, ukuran perusahaan dan rasio keuangan terhadap pengungkapan financial statement fraud - Damayanti, Milenia Nindi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
This study examines the effect of risk control, company size and financial ratios on financial statement fraud simultaneously and partially in banking companies listed on the Indonesia Stock Exchange in 2015-2020. In contrast to previous studies, this study measures risk control variables with ROI, Current Ratio and BOPO, company size with DAR, financial ratios with DER and uses earning management for financial statement fraud variables. This research uses a quantitative approach. The number of samples taken in this study were 18 companies from 47 banking companies within 6 years using purposive sampling method. Data processing in this study uses multiple analysis techniques using the SPSS 25 program which includes the classic assumption test with a significance (α) of 5%. Then partially this study shows the results that ROI has a significant positive effect on financial statement fraud, Current Ratio has a significant positive effect on financial statement fraud, BOPO has a significant positive effect on financial statement fraud, DAR has a significant negative effect on financial statement fraud, DER has a significant positive effect on financial statement fraud.